PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE BERBASIS ANIMASI PADA MATA PELAJARAN ANATOMI FISIOLOGI - Dian Maya Sari; Maulida Mutiara; Almaida Vebibina; Marnala Tobing (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development of Animation-based Articulate Storyline learning media for Anatomy and Physiology subjects. The research was conducted at SMK Negeri 1 Lubuk Pakam in the odd semester using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The first stage involved identifying potential problems by analyzing teachers’ and students’ needs. The second stage focused on data collection, followed by the third stage, which was product design. The fourth stage involved product validation by media experts, and the fifth stage included revising the media based on feedback. Validation results for the Animation-based Articulate Storyline learning media in Hair Anatomy and Physiology showed that the media aspects achieved 87.3% in the “good” category, while the material aspects achieved 79.5% in the “good” category. It can be concluded that the Animation-based Articulate Storyline learning media is feasible and suitable as a learning aid for students.